The relationship between physical activity and physical fitness among adolescents aged 15–16 years - Baihaqi, Yordan; Kusumawardhana, Buyung; Wiyanto, Agus; Siregar, M. Jamaludin (Sriwijaya Journal of Sport, 2026)
Research Background: Physical activity plays an important role in shaping students' physical fitness, which affects their physical and mental readiness to participate in physical education classes. However, empirical studies that specifically examine the relationship between physical activity and physical fitness of 10th grade high school students using the Indonesian Physical Fitness Test in the context of public schools in Semarang City are still limited. Differences in school environment characteristics and students' physical activity patterns indicate the importance of context-based research to obtain a more relevant empirical picture. Research Objective: This study aims to analyze the relationship between the level of physical activity and physical fitness of 10th grade students at Semarang State High School 10. Method: This study used a quantitative approach with a correlational method. The research sample consisted of 30 students selected using cluster sampling with one class as a cluster. Physical activity was measured using the International Physical Activity Questionnaire–Short Form (IPAQ-SF) questionnaire, while physical fitness was measured using the Indonesian Physical Fitness Test for the 16–19 age group. Data analysis was performed using Spearman's correlation test. Results: The results of the study indicate that most students have low levels of physical activity and their physical fitness levels are in the poor category. Correlation analysis shows that there is no significant relationship between physical activity and physical fitness among 10th grade students at State Senior High School 10 in Semarang. Conclusion: This study concludes that the physical activity performed by students has not contributed significantly to their physical fitness, indicating that the quality, intensity, and regularity of physical activity are not yet optimal. These findings have important implications for physical education teachers to design more structured physical activities oriented towards improving physical fitness. Further research is recommended to use more objective measurement instruments and involve other supporting variables to obtain a more comprehensive understanding.